A case report—Two manufacturers SAB testing kits can reveal different HLA antibody profiles—Identifying prozone and denatured antigen. (12th May 2020) - Battle, Richard K.; Henderson, Lorna; Phelan, Paul J.; Latham, Katy; Turner, David M.
Abstract : Recent reports have identified that the presence of non‐native conformation HLA to which antibody can bind upon Luminex HLA Class I single antigen beads, can vary in levels between different manufacturers kits and that the prozone effect may also be specific to particular products. We present a case in which both prozone and non‐native HLA reactive antibodies were observed, which raises important questions on how SAB assays are utilised, especially in the post‐transplant monitoring setting. A 56‐year old, highly sensitised female patient awaiting a regraft received a HLAi renal transplant. Post‐transplant monitoring showed discordant results between two SAB manufacturers assays, with one assay identifying a potential de novo HLA DSA. HLA Class I antibody reactivity was observed which was directed towards the Bw6 public epitope, which is present upon HLA molecules encoded for by numerous HLA‐B alleles. However in the day 19 post‐transplant sample reactivity spread beyond the Bw6 epitope. To investigate the possibility of a prozone type effect influencing the testing kit the day 19 post‐transplant sample was diluted 1:10 with PBS and reanalysed. After dilution the Bw6 reactivity was observed again, however the suspect de novo DSA still persisted. An analysis of the mismatched epitopes identified one manufacturer's assay as being confounded by the presence of denatured reactivity as well as prozone.